The Effect of Implementing 3S (SIND, SINO, SINI)-based Orthopedic Nursing Care Instrument in Improving Nursing Service Quality and Patient Safety in Indonesia Hospital - Sunadi, Apri; Nursalam, Nursalam; Sukartini, Tintin; Ahsan, Ahsan; Kolomboy, Fajrillah (Poltekita: Jurnal Ilmu Kesehatan, 2024)
Along with the increasing of orthopedic disorders incidence, the provision of orthopedic nursing care in Indonesia is also increasing. The Indonesian National Nurses Association (INNA) has published nursing care standards as a reference for nurses in providing nursing care and standardizing nursing care terminologies. Standard-based orthopedic nursing care instruments have been developed, but their effectiveness has not been investigated in improving the quality of nursing services and patient safety. This study aimed to identify the effect of the application of 3S-based Orthopedic Nursing Care (3S-ONC) on the quality of nursing services and patient safety. Descriptive quantitative analysis using a quasi-experimental method with a pretest and posttest with control group design, involving 106 respondents (53 control, 53 intervention), recruited by purposive sampling technique. In the intervention group, nurses provided nursing care by applying the 3S-based Orthopedic Nursing Care (3S-ONC) instrument. The study showed that in both groups, most of the nurses were in the early adult category, dominated by female sex and most of them had professional education level. There were significant differences in the quality of nursing services (p 0.046; α 0.05) and patient safety (p 0.000; α 0.05) between the intervention group and the control group after the application of the 3S-ONC instrument. The 3S-ONC instrument can improve the quality of nursing services and the safety of patients with orthopedic disorders in hospitals.The 3S-ONC instrument can be considered for the development of a paper-based or computer-based nursing care documentation system to further improve the quality of nursing services and patient safety in healthcare facilities, especially in hospital.